Constituents of Desmodium salicifolium (Poir.) DC (Fabaceae) with antifungal activity. (August 2022) - Donkia, Aphalaine P.T.; Eckhardt, Paul; Tsafack, Borice T.; Tchuenguem, Roland T.; Groß, Jonathan; Ponou, Beaudelaire K.; Teponno, Rémy B.; Dzoyem, Jean P.; Opatz, Till; Barboni, Luciano; Tapondjou, Léon A.
Abstract: Phytochemical investigation of the roots of Desmodium salicifolium led to the isolation of two new compounds (Desmoflavanone A: 5, 2', 4'-trihydroxy-4'', 4''-dimethyl-2 H -dihydropyranoisoflavanone (1 ) and desmodioside A: (22 R )-3 β, 22, 23-trihydroxyolean-12-en-3- O - α - L -rhamnopyranosyl-(1→2)-β-D -glucopyranosyl-(1→2)- β -D -glucuronopyranoside (2 )) together with nine known secondary metabolites including kaikasaponin III (3 ), spinosin (4 ), isovitexin (5 ), β -sitosterol 3- O - β -D -glucopyranoside (6 ), neorautenol (7 ), kaempferol (8 ), oleanolic acid (9 ), betulinic acid (10 ), and lupeol (11 ). The structures of these compounds were elucidated mainly by extensive spectroscopic analysis, particularly 1D and 2D NMR spectroscopy, electrospray ionization-mass spectrometry and by comparison of their spectroscopic data with those of related compounds reported in the literature. The methanolic extract, EtOAc and n -BuOH fractions as well as some isolated compounds were assessed for their antifungal activities against two fungi using microdilution method. The methanolic extract displayed weak activity against Candida albicans (MIC = 512 µg/mL). The EtOAc fraction also exhibited weak inhibitory effect with MIC of 256 µg/mL against Candida albicans and Candida glabrata . Compound 3 showed moderate effect against Candida glabrata with MIC value of 16 µg/mL while 1 was inactive against both fungi. Graphical Abstract: ga1 Highlights: This is the first phytochemical study on Desmodium salicifolium (Poir.) DC. A new isoflavanone and a new saponin were isolated together with nine known secondary metabolites. The major isolated compounds were tested for their antifungal activity.